A Writer's House in Wales - Morris, Jan (Washington, D.C. National Geographic, 2002)
The author describes Trefan Morys, her country house in Wales, and looks at Welsh culture, history, and symbols.
Include Map and Bibliography
Keywords: Wales - Social life and customs -- Manners and Customs -- Morris, Jan, -- 1926- -- Homes and haunts -- Wales. -- Morris, Jan, -- 1926- -- Homes and haunts -- Wales, North